Web-Based Service Status Monitoring Information System to Improve Service Efficiency: A Case Study of Kingsmith Store Sunter Repair Service - Mangadil, Christian; Sianipar, Anton Zulkarnain (Jurnal Teknologi Informatika dan Komputer, 2025)
Advances in information technology have driven significant changes in various industrial sectors, including after-sales service. This development has driven the transformation of customer service towards a faster, more transparent, and digital-based approach. Kingsmith Store Sunter, a fitness equipment repair service provider, still uses a manual system for communicating service status to customers, resulting in delayed information, operational inefficiencies, and low customer satisfaction. This study aims to develop and analyze the implementation of a web-based service status monitoring information system to improve service efficiency and quality. The study employed a descriptive qualitative approach with a single case study strategy. Data collection techniques included observation, interviews, documentation, and literature review. The system was developed using the Waterfall method, using the PHP programming language and a MySQL database. Key features include service data input by the admin and real-time service status searches by customers via serial number (SN) without the need to log in. The results show that this system successfully improves service time efficiency, data recording accuracy, and information transparency. Customers can monitor service progress independently, while admins can manage data in a more structured and faster manner. This system also improves customer satisfaction and reduces the burden of manual communication. Thus, this information system is a practical solution to support the digitalization of after-sales services and can be adopted by similar service providers in other sectors.